Radiological Outcome of Fracture of Neck of Femur Treated with Two versus Three Cannulated Screws Fixation in Adults - Tariq Ahmad, Abdus Samad Khan, Waleed Ali, Waqar Ahmed, Muhammad Younas, Lubna Shah (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: Adults with neck-of-femur fractures will be compared between two and three cannulated screws for fixation in this study. Study Design: Comparative/Experimental study Place and Duration: Orthopaedics and Trauma Department of Bacha Khan Medical College, Mardan and the department of Orthopaedics, Gambat Institutes of Medical and Science, Sindh during the period from April 2021 to September 2021 Methods: There were 90 patients of both genders had garden type fractures of neck of femur with ages 15-55years were included. Age, gender, and the reason of the fracture were among the variables collected after patients provided written consent. Patients were equally segregated into two groups. Group I had 45 patients and received cannulated screws fixation and in group II 45 patients received three cannulated screws fixation. Post treatment radiological union was assessed and compared at the 14th week. We used SPSS 23.0 to analyze complete data. Results: There were majority males 75 (83.3%) and only 15 (16.7%) females in this study. Most common cause of fracture was road accidents found in 65 (72.2%) cases followed by falling from height in 18 (20%) cases and sports in 7 (7.8%) cases. In group I mean age of the patients was 34.9±7.16 years and had mean BMI 23.6±3.22 kg/m2 while in group II mean age was 35.2±3.61 years with mean BMI 24.2±2.19 kg/m2. Mean union time in group I was 9.1±3.16 weeks and in group II mean time was 13.3±4.14 weeks. Frequency of radiological union in group I was higher among 43 (95.6%) cases as compared to group II in 37 (82.2%) cases. Overall success rate of radiological union was found among 88.9% cases. Conclusion: We concluded in this study that two cannulated screws fixation was effective and useful as compared to three cannulated screws fixation in the management of fracture of neck of femur in terms of less radiological union time and higher number of success rate among all cases.